Perioperative olfactory dysfunction in patients with meningiomas of the anteromedial skull base. Issue 4 (28th February 2019) - Hendrix, Philipp; Fischer, Gerrit; Linnebach, Alan‐Christopher; Krug, Julian B.; Linsler, Stefan; Griessenauer, Christoph J.; Oertel, Joachim
Abstract : Olfactory dysfunction represents a main symptom in olfactory groove meningiomas (OGM). Besides this, olfactory function has been sparsely investigated in patients suffering from supratentorial meningiomas. Here, the authors explore pre‐ and postoperative variables associated with olfactory dysfunction in supratentorial meningioma patients. This is a retrospective study on supratentorial meningioma patients who underwent meningioma resection between January 2015 and January 2016. Preoperative and postoperative olfactory performance was quantified using a lateralized sniffin' stick odor identification test. Meningiomas affecting the olfactory system ( n = 23) were compared to meningiomas in other locations among the control group ( n = 40). Meningiomas that affected the olfactory system had odds of 3.6 and 3.7 in being associated with ipsilateral (lesional) and bilateral anosmia, respectively. Subgroup analysis revealed that meningiomas causing a midline shift across the frontal base and older age represented risk factors for preoperative anosmia. The odds of experiencing acquired postoperative ipsilateral anosmia were significantly increased in olfactory system affecting meningiomas (OR 11.1). Subgroup analysis highlighted OGMs to represent the predominant location associated with deterioration. General surgical complications predisposed patients to loss of contralateral (OR 12.3) and bilateral olfactory function (OR 27.8). Older age and meningiomas causing a midline shift across the frontal base predispose patients to preoperative olfactory dysfunction. Resection of OGMs and surgical complications are risk factors for postoperative olfactory deterioration to anosmia. Likely, olfactory dysfunction is underrecognized even in OGMs. In OGM surgery, however, preoperative lateralized testing might be critical to selecting an appropriate surgical route to preserve olfactory function. Clin. Anat. 32:524–533, 2019. © 2019 Wiley Periodicals, Inc.